SN- and NS-puckered sugar conformers are precursors of the (6–4) photoproduct in thymine dinucleotide. Issue 11 (7th March 2022) - Jakhlal, Jouda; Denhez, Clément; Coantic-Castex, Stéphanie; Martinez, Agathe; Harakat, Dominique; Douki, Thierry; Guillaume, Dominique; Clivio, Pascale
Abstract : The S conformation of at least one sugar residue in the TT site is crucial for (6–4) PP formation. This S sugar can be located at the 5′- or 3′-end of the TT site. The 5′-end S conformer location is the most efficient at providing (6–4) PP. Abstract : Some amount of furanose in a southern conformation, possibly in both, but certainly in one of the two adjacent nucleotides of a dipyrimidine site, is necessary for (6–4) photoproduct formation in oligonucleotides. To explore the necessity, role, and most favorable location of each South sugar conformer in the formation of the (6–4) adduct in the thymine dinucleotide TpT, the photochemical behavior of two synthetic analogues, in which the South sugar conformation is prohibited for one of their two sugars, has been examined. Herein, we experimentally demonstrate that the presence of one sugar presenting some amount of South puckering, at any of the extremities, is sufficient to trigger (6–4) adduct formation. Nonetheless, the photochemical behavior of the dinucleotide with a South-puckered conformation at the 5′-end, mimics more closely that of TpT. In addition, using the 5′ North 3′ South-dilocked dinucleotide, we demonstrate that the flexibility of the South pucker at the 3′-end has little influence on the (6–4) adduct formation.